Peter Polack, Guerrilla Warfare: Kings of Revolution (Historia, 2021)
"The only certain thing is that history will repeat itself" (p 13), is argued by Peter Polack in his book titled Guerilla Warefare: Kings of Revolution. This publication provides a collection of biographies of ten notable guerilla leaders who could serve as an inspiration to modern-day strategists, military personell and politicians.